Las actividades lúdicas para potenciar la psicomotricidad gruesa en las niñas y niños de 4 a 5 años de la unidad educativa Dr. Manuel Agustín Cabrera Lozano de la ciudad de Loja, cantón Loja, provincia de Loja, periodo 2014-2015 - Gonzalez Medina, Maria Eugenia (2016)
This research includes a study of leisure activities to enhance gross motor skills in children from 4-5 years Education Unit Dr. Manuel Agustín Lozano Cabrera of the City of Loja, Loja Canton province of Loja, period 2014 -2015. The overall objective of contributing to the development of this research work was: Contribute to the development of gross motor skills through play activities for children from 4-5 years attending the Education Unit Dr. Manuel Agustín Lozano of Cabrera Loja, 2014-2015. The methods used throughout the research process were: the scientific method, analytic-synthetic method, hermeneutical method and statistical method. Observation technique was used and as a tool for gathering information Exámen Psychomotor de la Primera Infancies engine was applied. The research population consists of 24 children. The results obtained in implementing the instrument were found that 64% of children have good postural control, and 36% do not. So it is concluded that the children do not perform recreational activities properly.